‘The South! something exclaims within me’: Real and Imagined Spaces in Italy and the South in Vernon Lee’s Travel Writing - Leonie Wanitzek (Cahiers Victoriens et Edouardiens)
Literary criticism on Vernon Lee has so far focused little on either her seven published collections of travel essays or on her intense engaging with space and place in her writing. This paper considers Lee’s essays on Italy, her adopted country of residence, as a nuanced and complex contribution to late Victorian and Edwardian visions of the South. Lee’s essays – published between 1897 and 1925 but all written before World War I – construct two distinct but related tropes of ‘Italy’ and ‘the South’. These visions of ‘the South’ and ‘Italy’ are embodied in specific locations but they also serve as mental spaces of absence and longing. Throughout the essays, the idea of the genius loci or spirit of places is crucial to Lee’s understanding of place and the perception of space. Sensory impressions interact with memories, intertextual associations and feelings of nostalgia in order to produce Lee’s intense and personal emotional reactions to places. Edward Soja’s concept of ‘Thirdspace’, or ‘real-and-imagined places’ further allows me to explain Lee’s experiences of place as encounters between the real and the imagined, the present and the remembered. I argue that the topoi of ‘the South’ and ‘Italy’ function as mental ‘Secondspaces’ which combine with the geographical ‘Firstspaces’ of Lee’s travels in order to produce complex Thirdspace depictions of Italian places.